FINANCIAL LITERACY AND RISK PERCEPTION: THE KEY TO UNDERSTANDING THE RELATIONSHIP BETWEEN FOMO AND INVESTMENT DECISIONS - Goeyana, Agnes; Marlina, Maria Asumpta Evi (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The study of consumer behavior has made Fear of Missing Out (FOMO) a significant concern, particularly concerning Generation Z, who grew up in an increasingly connected digital era. The study's central issue is the FOMO phenomenon and its effect on Generation Z's investment decisions in entrepreneurial universities. Through an analysis of the role of financial literacy and risk perception as mediators, this paper seeks to understand how Generation Z's investment decisions are influenced by FOMO, particularly in the context of an entrepreneurial university. This study employs the Partial Least Square-Structural Equation Model (PLS-SEM) analysis model in a descriptive quantitative manner. The study's sample comprises 358 Generation Z students at Ciputra University Surabaya's Faculty of Business and Management. According to the study's findings, generation Z's investment decisions at entrepreneurial universities are positively and significantly impacted by FOMO. Financial literacy is a mediating variable in the relationship between FOMO and Generation Z investment decisions at entrepreneurial universities; risk perception is a mediating variable in the relationship between FOMO and Generation Z investment decisions at entrepreneurial universities. These findings suggest that strategies are needed to address FOMO and improve financial literacy and risk perception management among Generation Z students to improve the investment decisions of Generation Z students in entrepreneurial universities.